Identification of specific recommendations for prehospital stroke care associated with shorter door-to-CT times – An analysis of Get with the Guidelines-Stroke registry and prehospital data - Dylla, Layne; Higgins, Hannah M.; Wham, Courtney D.; Leppert, Michelle; Ravare, Brandy C.; Jeppson, Kerri A.; Bina, Heather T.; Monte, Andrew A.; Poisson, Sharon N. (Frontiers in Stroke, 2024)
Objective Full compliance with American Heart Association (AHA) recommendations for prehospital care of stroke patients remains low. This study aims to identify components of prehospital care associated with shorter door-to-computed tomography (CT) times. Methods Data from a comprehensive stroke center's Get with the Guidelines-Stroke registry were supplemented by prehospital medical records for ischemic stroke patients between January 1, 2018, and December 31, 2020. Descriptive statistics and multivariable linear regression modeling was used to evaluate door-to-CT times for encounters compliant with AHA recommendations. Results There were 621 ischemic stroke patients who presented via a prehospital provider, 452 of whom presented from the scene. Without adjusting for potential confounders, shorter door-to-CT times were observed with emergency medical services' documentation of a last-known well time, measurement of a blood glucose level, prenotification of a suspected stroke, or full compliance with AHA recommendations. Documentation of classic stroke signs, but not of a prehospital stroke scale, was also observed to have shorter door-to-CT times compared to encounters in which this did not occur. Conclusion During prehospital care of stroke, documentation of classic symptoms, obtaining a last-known well time or time of symptom onset, obtaining a blood glucose level, prenotifying the receiving hospital of suspected stroke, and complying fully with guidelines are associated with shorter door-to-CT times. Further studies are needed to understand if a shift in prehospital provider education, focusing on these key components of care, could lead to earlier diagnosis and treatment of acute stroke.